Application of Ultra Fine Bubble Addition to Diesel Fuel on The Performance of Agricultural Transport Vehicle Engines - Ardiansyah, Ahmad; Herodian, Sam; Supriyadi, Faqih; Abriyant, Riva Yudha; Wibowo, Cahyo Setyo (Testing Center for Oil and Gas LEMIGAS, 2025)
Diesel engines have long been the primary choice across various industrial sectors, including agricultural transport vehicles. However, energy efficiency and fuel consumption remain significant challenges. One approach to address these issues is the application of Ultra Fine Bubble (UFB) technology to diesel fuel, which aims to enhance physical fuel properties and improve combustion efficiency. This study was conducted to evaluate the effect of UFB treatment on B0 CN-51 and B40 fuels in relation to fuel quality and diesel engine performance. The fuel characterization tests showed that the calorific value of B0 CN-51 increased from 43.73 MJ/kg to 45.68 MJ/kg, and B40 from 42.46 MJ/kg to 42.94 MJ/kg. The cetane number also increased, accompanied by a reduction in sulfur content and lubricity. Performance testing using a chassis dynamometer indicated improvements in maximum power and torque. B0 CN-51 UFB produced 95.68 kW of power and 344.18 Nm of torque, while reducing specific fuel consumption (SFC) from 42.25 to 39.82 g/kWh. In addition, fuel consumption in ℓ/100 km decreased significantly, with an average reduction in efficiency of up to 4.85%. For B40, SFC decreased from 44.99 to 43.75 g/kWh, with an average consumption reduction of 1.73%. These results demonstrated that UFB can significantly improve diesel engine performance and fuel efficiency.